2008
DOI: 10.3892/ijo.32.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cell death induced by spermine and amine oxidase in mouse melanoma cells

Abstract: Abstract. Polyamines such as spermine, spermidine and putrescine are necessary for cell proliferation and are detected at higher concentrations in most tumor tissues, compared to normal tissues. The amine oxidase enzymes can generate cytotoxic products such as hydrogen peroxide and aldehydes from these polyamines. This study investigates the mechanisms of cell death in B16-F0 mouse melanoma tumor cells exposed to bovine serum amine oxidase and exogenous spermine. The bovine serum amine oxidase/spermine enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…It has been reported that MDR cells contain more specific lipids than WT cells, such as sphingolipids, phosphatidylinositol, cholesterol, and cholesterol esters, and thus degree of lipid peroxidation has been suggested as a surrogate for the influence of ROS on MDR cells [41,[43][44][45]. It has also been confirmed that MDR cells are more sensitive to H 2 O 2 and aldehyde, the products of lipid peroxidation, than their WT counterpart [14,17,18]. Recently acrolein, a highly reactive aldehyde produced by lipid peroxidation, has been found to cause apoptotic cell death mediated by endoplasmic reticulum stress [46].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It has been reported that MDR cells contain more specific lipids than WT cells, such as sphingolipids, phosphatidylinositol, cholesterol, and cholesterol esters, and thus degree of lipid peroxidation has been suggested as a surrogate for the influence of ROS on MDR cells [41,[43][44][45]. It has also been confirmed that MDR cells are more sensitive to H 2 O 2 and aldehyde, the products of lipid peroxidation, than their WT counterpart [14,17,18]. Recently acrolein, a highly reactive aldehyde produced by lipid peroxidation, has been found to cause apoptotic cell death mediated by endoplasmic reticulum stress [46].…”
Section: Discussionmentioning
confidence: 85%
“…Reactive oxygen species (ROS)-generating enzymes have also been explored to overcome MDR in cancer cells [12][13][14][15][16][17][18] based on the knowledge that cancer cells express higher ROS levels than normal cells and MDR cells are more susceptible to excess exogenous ROS than non-resistant cells [19][20][21][22][23][24][25][26][27]. Indeed, ROS-generated by the enzyme bovine serum amine oxidase (BSAO) caused higher toxicity in Pgp-expressing MDR cells than wild-type cells [12][13][14] and MDR cells were more sensitive to the enzymatic reaction products H 2 O 2 and aldehyde than their wild-type counterpart cells [17,18]. Moreover, excess ROS was found to down regulate Pgp in MDR cells contributing to the reversal of the MDR phenotype [16,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among polyamines, spm was most effective in inhibiting cancer cell growth. The cytotoxicity of spm has been suggested by the production of H2O2 and aldehyde(s) from spm in the presence of amine oxidase [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Among polyamines, spm was most effective in inhibiting cancer cell growth. The cytotoxicity of spm has been suggested by the production of H2O2 and aldehyde(s) from spm in the presence of amine oxidase [1,2].Polyamines are also essential for the normal attachment of cells to the extracellular matrix (ECM), which explains at least some of the reliance of cell migration and the organization of the cytoskeleton on normal polyamine levels [22]. The migration of cells depends on their ability to make and break attachments to the ECM.…”
mentioning
confidence: 99%